Development of graphic symbols based on tropical plant images in decorative tiles production - Megat Nizar, Megat Muzhafar; Musllim, Zulkifli (Faculty of Design & Architecture, Universiti Putra Malaysia, 2012)
The most important aspect of choosing tile is the pattern design. Therefore the importance of focusing the production process in design has become crucial. The biological, physical and visual aspects of environment influence life philosophy, culture, society, tradition and creativity development. In the production of design symbols, it is evident that there is lack of focus and assessment given to the production process compared to that of the end product. The importance of the transformation process is emphasized by Wallschlaeger and Cynthia Busic-Synder who believe that the problem solving processes are shown to illustrate how the process can be altered for use in solving specific types of problem in design. Therefore, the objectives of this research are to determine the significance of systematic design process and ideas transformation in the development of graphic symbol. This study explores the relationship between tiles production and its pattern within an activity theory framework, focusing on data collected using questionnaires survey from selected universities in Peninsular Malaysia and interviews at Design Department of selected manufacture in Peninsular Malaysia. At the conclusion of this paper, a design criteria and analysis of system will be developed before production process of decorative tiles design from tropical plants images